2022
DOI: 10.3390/ma15238657
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Matrix Composites Obtained by the Reactive Sintering of Boron Carbide with Intermetallic Compounds from the Ti-Si System

Abstract: In this study, we investigated the effect of adding two different intermetallics, Ti5Si3 and TiSi2, for the preparation of TiB2-SiC-B4C composites. As part of the research, stoichiometric composites consisting only of two phases TiB2 and SiC were obtained. The TiB2-SiC-B4C composites were prepared via pressureless sintering. The presence of the phases in the sintered composites was confirmed using X-ray diffraction and scanning electron microscopy. The SEM-EDS examination revealed that the TiB2 and SiC phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Combination of these properties makes TiB 2 an ideal candidate for use in ballistic armors, crucibles, metal evaporation boats, cutting tools, wear resistance parts, and cathodes for alumina smelting [ 4 , 5 , 6 ]. Many ceramic phases, such as Al 2 O 3 , SiC, B 4 C, and MgAl 2 O 4 , have been considered as the reinforcement to improve fracture toughness, oxidation resistance, heat resistance, and mechanical strength of the TiB 2 -based composites [ 7 , 8 , 9 , 10 ]. Moreover, a recent study showed that TiB 2 –Al 2 O 3 –MgAl 2 O 4 composite possesses temperature insensitive and enhanced microwave absorption properties [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combination of these properties makes TiB 2 an ideal candidate for use in ballistic armors, crucibles, metal evaporation boats, cutting tools, wear resistance parts, and cathodes for alumina smelting [ 4 , 5 , 6 ]. Many ceramic phases, such as Al 2 O 3 , SiC, B 4 C, and MgAl 2 O 4 , have been considered as the reinforcement to improve fracture toughness, oxidation resistance, heat resistance, and mechanical strength of the TiB 2 -based composites [ 7 , 8 , 9 , 10 ]. Moreover, a recent study showed that TiB 2 –Al 2 O 3 –MgAl 2 O 4 composite possesses temperature insensitive and enhanced microwave absorption properties [ 11 ].…”
Section: Introductionmentioning
confidence: 99%